(untitled) (Jurnal Pembangunan Sosial, 2024)
This concept paper is a discussion that emphasizes the virtual reality support idea. Widad FAROKAM is an application based on the system that is compatible with the website surfed by mobile or desktop. The future target user of this system will rehearse the attention of completing the task given and divert their attachment growth by the involvement of a guardian within the task target. Still, the research must explore certain aspects which indeed can make up several issues arise. Widad FAROKAM’ integrated system is based on the currently developed product of R&D named Widad Psychetra Door (WPD). Through the investigation and feasibility study from the same research in a previous paper published on Widad FAROKAM & WPD, the common representation arises from the fourth phase of this R&D product. This fourth phase involved virtual reality.